Diagnostic issues dealing with the management of teeth with vertical root fractures: a narrative review - Stefano Corbella; Aviad Tamse; Carlos Nemcovsky; Silvio Taschieri (Ariesdue, 2014)
Aim: The objectives of this study were to review the existing literature of vertical root fractures (VRFs) dealing with its management and to describe a classification for the bone defects resulting after extraction. Methodology: An electronic search was performed on biomedical databases using a combination of appropriated search terms combined through the use of Boolean operators. A classification of the bone defects associated with vertical root fracture (VRF) was also proposed. Results: Outcomes data extracted from the selected articles were summarized. Conventional radiography could fail in directly detecting the presence of VRF but can allow finding bone resorption areas which are related to the fracture itself. Tridimensional radiography (CBCT) may allow a better visualization of such bone defects. The bone defects associated to VRF could be classified on the basis of the number of walls affected and of the depth (in apico-coronal direction). Conclusions: The diagnosis of VRF is a challenging process that includes both clinical and radiographic examination. In most cases, when postextraction implant was placed, guided bone regeneration is required to compensate the bone defect caused by VRF. A deep knowledge of the characteristics of the associated bone defect may allow an immediate and predictable substitution with dental implants, when tooth extraction is the only option.